Application prospects of marine internet - Shengming JIANG; Xiang SHAN (Dianxin kexue)
The original intention of marine internet aims to extend the terrestrial internet to the marine environment (including underwater,surface and air) seamlessly as much as possible,providing internet services for users therein.However,there are still many other potential applications of the marine internet in such specific marine environments.These applications and main research issues were discussed briefly in order to call for more attentions to the R＆amp;D of marine internet.